Molecular identification technique of Trypanosoma evansi by Multiplex Polymerase Chain Reaction - Dyah H. Sawitri; April H. Wardhana; H. Wibowo; M. Sadikin; Fitrine Ekawasti (Indonesian Center for Animal Research and Development (ICARD), 2015)
Trypanosoma evansi is a Hemoflagella parasite that infects cattle and is known as the agents of Surra. Several other trypanosome species infects mammals: T. equiperdum, T. b. rhodesiense, T. b. gambiense, T. vivax, T. congolense, T.theileri. Some of these species is quite difficult to be distinguished morphologically with T. evansi through conventional techniques (thin blood smear). Molecular technique by polymerase chain reaction (PCR) is reported to have the ability to identify, characterize and diagnose trypanosomes accurately. However, a single PCR used is relatively expensive because it takes at least two or more pairs of primers to determine T. evansi. The purpose of this study is to develop T. evansi species identification techniques by multiplex PCR/mPCR (the three pairs of primer in one reaction) that takes the relatively fast and inexpensive. A total of 31 isolates T.evansi were obtained from Bblitvet Culture Collection (BCC) and the Department of Parasitology BBLitvet used in this study. Isolates represent isolates from endemic areas and Surra outbrake isolated from 1988-2014. DNA extraction performed on each sample, including Bang 87 isolates which has been purified as a positive control. Primers used are specific for T. evansi, the ITS-1, Ro Tat 1.2 VSG and ESAG 6/7. Before running mPCR, each primer is optimized by using a single PCR. The results showed that the three primers can be combined in a single reaction with mPCR technique and amplify each DNA fragment target perfectly, so identified 31 isolates as T. evansi. This technique can be applied in the field with a lower cost and faster time.Key Words: Trypanosoma evansi, Identification, Multiplex PCR